A word about Ukraine’s flagship of marine sciences (towards V. I. Starostenko’s 90th anniversary) - Shchiptsov, O.A. (Geofizicheskiy Zhurnal, 2025)
The article is dedicated to V.I. Starostenko, an outstanding Ukrainian geophysicist who has significant and diverse experience in organizing strategically important events for domestic science. He took an active part in many marine expeditions and conducting research within the framework of international scientific programs and projects. The results of scientific expeditions obtained in various water areas of the World Ocean became the basis for writing fundamental works devoted to the structure of the Earth’s crust and upper mantle.